Recuperação de imagens digitais com base na distribuição de características de baixo nível em partições do domínio utilizando índice invertido - Proença, Patrícia Aparecida (2010)
The main goal of a images retrieval system is to obtain images from a collection that assist a need of the user. To achieve this objective, in generally, the systems of retrieval of images calculate the similarity between the user's need represented by a query and representations of the images of the collection. Such an objective is dicult of being obtain due to the subjectivity of the similarity concept among images, because a same image can be interpreted in dierent ways by dierent people. In the attempt of solving this problem the content based image retrieval systems explore the characteristics of low level color, forms and texture in the calculation of the similarity among the images. A problem of this approach is that in most of the systems the calculation of the similarity is accomplished being compared the query image with all of the images of the collection, turning the dicult and slow processing. Considering the indexation of characteristics of low level of partitions of digital images mapped to an inverted index, this work looks for improvements in the acting of the processing of querys and improve in the precision considering the group of images retrieval in great bases of data. We used an approach based in inverted index that is here adapted for partitions images. In this approach the concept of term of the retrieval textual, main element of the indexation, it is used in the work as characteristic of partitions of images for the indexation. Experiments show improvement in the quality of the precision using two collections of digital images.